Infection management processes in intensive care and their association with mortality. (30th March 2021) - Fitzpatrick, Leigh P; Levkovich, Bianca; McGloughlin, Steve; Litton, Edward; Cheng, Allen C; Bailey, Michael; Pilcher, David
Abstract: Background: ICU-specific tables of antimicrobial susceptibility for key microbial species ('antibiograms'), antimicrobial stewardship (AMS) programmes and routine rounds by infectious diseases (ID) physicians are processes aimed at improving patient care. Their impact on patient-centred outcomes in Australian and New Zealand ICUs is uncertain. Objectives: To measure the association of these processes in ICU with in-hospital mortality. Methods: The Australian and New Zealand Intensive Care Society (ANZICS) Adult Patient Database and Critical Care Resources registry were used to extract patient-level factors, ICU-level factors and the year in which each process took place. Descriptive statistics and hierarchical logistic regression were used to determine the relationship between each process and in-hospital mortality. Results: The study included 799 901 adults admitted to 173 ICUs from July 2009 to June 2016. The proportion of patients exposed to each process of care was 38.7% (antibiograms), 77.5% (AMS programmes) and 74.0% (ID rounds). After adjusting for confounders, patients admitted to ICUs that used ICU-specific antibiograms had a lower risk of in-hospital mortality [OR 0.95 (99% CI 0.92–0.99), P  = 0.001]. There was no association between the use of AMS programmes [OR 0.98 (99% CI 0.94–1.02), P  = 0.16] or routine rounds with ID physicians [OR 0.96 (99% CI 0.09–1.02), P  = 0.09] and in-hospital mortality. Conclusions: Use of ICU-specific antibiograms was associated with lower in-hospital mortality for patients admitted to ICU. For hospitals that do not perform ICU-specific antibiograms, their implementation presents a low-risk infection management process that might improve patient outcomes.